Studi Literatur: Implementasi Model Problem Based Learning melalui Pendekatan Deep Learning terhadap Keterampilan Proses Sains dan Hasil Belajar Siswa SMA - Niwanda Azela Putri; Jodion Siburian; Raissa Mataniari (Journal Innovation In Education, 2026)
The development of skills and deep conceptual understanding is a crucial requirement in 21st-century science learning. However, various studies have shown that learning practices in schools still tend to be oriented towards procedural delivery of material, thus under developing students' deep cognitive engagement and scientific skill development. Problem-Based Learning (PBL) and Deep Learning approaches are considered capable of creating more meaningful learning through authentic problem exploration, collaboration, and conceptual reflection. Previous research has generally examined these two approaches separately, resulting in limited synthetic studies specifically integrating PBL, Deep Learning approaches, and science process skills. This study aims to analyze the implementation of the PBL model with a Deep Learning approach on science process skills and learning outcomes of high school students through a Systematic Literature Review approach. A total of 20 relevant research articles were analyzed using a mixed-methods embedded synthesis technique. The results of the synthesis indicate that the application of PBL, combined with a Deep Learning approach, consistently improves students' science process skills, particularly in their ability to observe, formulate hypotheses, design experiments, analyze data, and draw scientific conclusions. Additionally, some studies have found significant improvements in learning outcomes compared to traditional learning methods. These findings provide a theoretical contribution to the development of science learning models that are more reflective, contextual, and oriented towards deep learning.